Probing the Importance of Charge Balance and Noise Current in WSe2/WS2/MoS2 van der Waals Heterojunction Phototransistors by Selective Electrostatic Doping. Issue 19 (18th August 2020) - Ra, Hyun‐Soo; Jeong, Min‐Hye; Yoon, Taegeun; Kim, Seungsoo; Song, Young Jae; Lee, Jong‐Soo
Abstract: Heterojunction structures using 2D materials are promising building blocks for electronic and optoelectronic devices. The limitations of conventional silicon photodetectors and energy devices are able to be overcome by exploiting quantum tunneling and adjusting charge balance in 2D p–n and n–n junctions. Enhanced photoresponsivity in 2D heterojunction devices can be obtained with WSe2 and BP as p‐type semiconductors and MoS2 and WS2 as n‐type semiconductors. In this study, the relationship between photocurrent and the charge balance of electrons and holes in van der Waals heterojunctions is investigated. To observe this phenomenon, a p‐WSe2 /n‐WS2 /n‐MoS2 heterojunction device with both p–n and n–n junctions is fabricated. The device can modulate the charge carrier balance between heterojunction layers to generate photocurrent upon illumination by selectively applying electrostatic doping to a specific layer. Using photocurrent mapping, the operating transition zones for the device is demonstrated, allowing to accurately identify the locations where photocurrent generates. Finally, the origins of flicker and shot noise at the different semiconductor interfaces are analyzed to understand their effect on the photoresponsivity and detectivity of unit active area (2.5 µm 2, λ = 405 nm) in the p‐WSe2 /n‐WS2 /n‐MoS2 heterojunction device. Abstract : By selectively applying electrostatic doping to a specific channel layer, a p‐WSe2 /n‐WS2 /n‐MoS2 heterojunction device with both p–n and n–n junctions can modulate the charge carrier balance between heterojunction layers to generate photocurrent upon illumination. The relationship between photocurrent and the charge balance of electrons and holes in van der Waals heterojunctions is investigated.